The scientists a history of science told through the lives of its greatest inventors - Gribbin, John R. (Random House, 2003)
Tells the story of the people who have made science, and of the times in which they lived and worked. Gribbin begins with Copernicus, during the Renaissance, when science replaced mysticism as a means of explaining the workings of the world, and continues through the centuries, creating an unbroken genealogy of not only the greatest but also the more obscure names of Western science, a dot-to-dot line linking amateur to genius, and accidental discovery to brilliant deduction.